Visual attraction of the European tarnished plant bug Lygus rugulipennis (Hemiptera: Miridae) to a water trap with LED light in chrysanthemum greenhouses and olfactory attraction to novel compounds in Y‐tube tests. Issue 6 (6th April 2022) - van Tol, Robert WHM; Diaz Rodriguez, Celia M; de Bruin, Antje; Yang, Daowei; Taparia, Tanvi; Griepink, Frans C
Abstract: BACKGROUND: The European tarnished plant bug Lygus rugulipennis Poppius (Hemiptera: Miridae) can cause several types of damage to crops grown in greenhouses and fields, including flower abortion in eggplant, stem and fruit damage in cucumbers, and splits in chrysanthemums. Studies suggest that both male and female L . rugulipennis may be more attracted to traps based on visual attraction than pheromone‐based trap. Therefore, the aim of this study was to evaluate the effectiveness of a water trap with LED lights and semiochemicals in trapping L . rugulipennis in the laboratory and greenhouse. RESULTS: The results showed that water traps equipped with white LED light caught 20 – 30 times more bugs than did the sex pheromone‐based traps in greenhouse experiment. During the week of peak flight, the LED water trap caught a total of 29 males and females, whereas the sex pheromone caught only one male. Among the semiochemicals tested in a Y‐tube, both males and females were attracted to ß ‐caryophyllene, but not in the presence of the sex pheromone, whereas both males and females were attracted to pentyl butyrate in the presence of the sex pheromone. The pheromone plus bean plant odor was attractive to the insects, suggesting an interaction between plant odor and pheromone. CONCLUSION: Overall, the findings of the study showed that the water trap with LED light could be an effective method for trapping L . rugulipennis in greenhouses. © 2022 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : An attractive water trap with white LED light catches 20 to 30 times more female and male Lygus rugulipennis than the sex pheromone trap.